Decision making, psychological wellbeing and psychosocial outcomes for high risk women who choose to undergo bilateral prophylactic mastectomy – A review of the literature. (August 2016) - Glassey, Rachael; Ives, Angela; Saunders, Christobel; Musiello, Toni
Abstract: A bilateral prophylactic, or preventative, mastectomy (BPM) for women at high risk of developing breast cancer (BC) can reduce their risk of developing the disease by up to 90% (relative risk reduction). An increasing number of women, including young women, are taking up this option. However, there is a dearth of information for younger women (under 40 years) choosing preventative mastectomy. In fact, no studies to date have specifically focused on younger women's experiences of a BPM and investigated their informational needs. The purpose of this review is to report on the current literature surrounding the psychological experience of a BPM and the informational needs for women at high risk of developing BC with a particular emphasis on younger women. Research has highlighted a range of psychological outcomes linked to preventative mastectomy, including positives such as reduced anxiety and negatives including impaired body image and sexuality. The literature strongly suggests women want more information surrounding BPM, particularly related to the after effects of the surgery, and the impact on their psychological wellbeing. Research method limitations and reporting has resulted in conflicting conclusions, making it difficult for women to be well informed. In particular, there has been little focus on the experiences and needs of younger women opting for BPM. Due to the unique needs of younger women and an increase in BPM rates for younger women, it is imperative that the needs of this group are addressed. Together these findings provide justification and recommendation for further research in this area. Highlights: No studies have focused specifically on younger women's experiences of BPM. Research strongly suggests women want more information surrounding BPM. Women report positives such as reduced anxiety and negatives such as body image. Limitations in design and method are found, notably the lack of qualitative studies.